1993
DOI: 10.1152/jappl.1993.75.6.2811
|View full text |Cite
|
Sign up to set email alerts
|

Nasal airway geometry: comparison between acoustic reflections and magnetic resonance scanning

Abstract: To evaluate the accuracy of the acoustic reflection (AR) technique for determination of nasal cavity cross-sectional areas, the area-distance function of both sides of the nose was determined in 10 subjects and compared with magnetic resonance imaging (MRI). Interindividual variation for the correlation between MRI and AR was seen, but in general the areas from 1 to 6 cm into the nasal cavity measured by AR were larger than areas measured by MRI, especially where the surface was most convoluted. The total volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
85
0
11

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 0 publications
2
85
0
11
Order By: Relevance
“…Terheyden et al (26) summarize several attempts to validate how precisely AR measures the nasal cavity in humans, including validation of AR by magnetic resonance (MR) imaging (2,8) and by a fluid-displacement method (FDM) (7). By comparing volumes determined by AR with volumes of nasal cavity casts, Kaise et al (12) found AR in guinea pigs to measure only 75% of nasal cavity volume.…”
mentioning
confidence: 99%
“…Terheyden et al (26) summarize several attempts to validate how precisely AR measures the nasal cavity in humans, including validation of AR by magnetic resonance (MR) imaging (2,8) and by a fluid-displacement method (FDM) (7). By comparing volumes determined by AR with volumes of nasal cavity casts, Kaise et al (12) found AR in guinea pigs to measure only 75% of nasal cavity volume.…”
mentioning
confidence: 99%
“…Other studies have highlighted the physical significance of transient breathing (Shi et al, 2006), inlet velocity profiles (Keyhani et al, 1995;Subramaniam et al, 1998), nasal wall motion (Fodil et al, 2005), nasal valve change (Bridger 1970;Bridger and Proctor 1970) and glottal aperture variation (Brancatisano et al, 1983;. Moreover, each nasal model in this study is based on images of one single subject and does not account for the intersubject variability (Hilberg et al, 1993;Pickering and Beardsmore 1999). Another limitation is the typical supine position of the subjects during data acquisition, which is different from normal breathing while awake.…”
Section: Discussionmentioning
confidence: 98%
“…Eine direkte Schwellungserfassung in der Nase ist ebenfalls mit der Computertomographie und der Magnetresonanztomographie [3,8,12] möglich. Hier kön-nen endonasale geometrische Verhältnis-se korrekt abgebildet werden.…”
Section: Mögliche Verfahrenunclassified
“…Die Ankopplung des Ultraschalles erfolgt dabei durch Gel oder Flüssigkeit in der Nase. Bewegungsartefakte werden durch eine Bissschiene verhindert [24,25].Eine direkte Schwellungserfassung in der Nase ist ebenfalls mit der Computertomographie und der Magnetresonanztomographie [3,8,12] möglich. Hier kön-nen endonasale geometrische Verhältnis-se korrekt abgebildet werden.…”
unclassified